Evaluation of lake water quality in Klang valley using multivariate statistical techniques - Hafizan, Juahir; Azman, Azid; Isa Baba, Koki; Sharifuddin, Md. Zain; Hin, Kow Kah (2016)
Lakes are major sources of water for human consumption, domestic uses, and recreational purposes in Malaysia, but suffered deterioration in water quality due to anthropogenic activities. This study investigates the Physico chemical parameters and heavy metals distribution of five selected lakes at Klang Valley in Malaysia to evaluate its quality status and possible sources of the identified pollutants. The physicochemical parameters analyzed were Dissolved Oxygen, pH, Biological Oxygen Demand, Ammoniacal Nitrogen and metals include Cd, Mn, Pb, As, and Fe. The levels of these parameters were compared to Malaysia’s interim national water quality standard. The multivariate statistical analysis methods applied were Hierarchical cluster analysis (HCA) and Principal component analysis (PCA). The PCA shows PC1 is strongly loaded with AN and Mn, and negative loading with DO and pH, while PC2 was strongly loaded with As, Cd, Pb and Fe. HCA classified the sample sites into three clusters, and the results showed variations in degree of pollution due to oxygen consuming organic pollutants possibly from domestic sewage, waste water, and other anthropogenic sources. The lakes were classified as the most polluted, polluted and less polluted. There is a need to monitor the lakes to prevent further deterioration. Proper lake management and environmental law enforcements will assist in maintaining a healthy lake ecosystem.